An evidence summary of the management of patients taking direct oral anticoagulants (DOACs) undergoing dental surgery. Issue 5 (May 2016) - Johnston, S.
Abstract: Direct oral anticoagulant (DOAC) drugs (dabigatran, rivaroxaban, and apixaban) have emerged in the last decade to overcome some of the drawbacks of existing medications. To date, little is known about the dental management of patients taking these drugs. This study was undertaken to establish the evidence for the management of patients undergoing dental procedures while taking these medications. A rapid review approach was used to identify clinical and scientific research related to dental surgery performed in patients taking DOACs in order to produce an evidence summary. The rapid review did not identify any systematic reviews or original clinical trials and the overall quality of evidence found was poor. Most of the literature consisted of non-structured review articles and guidance documents based on assumptions from non-dental data and expert opinion, and recommendations on best practice varied throughout. The findings from the review of the literature varied considerably. Currently, recommendations are based on poor quality scientific data and clinical trials are required to establish best evidence-based practice guidance.